The neural mechanisms of visual selection: the view from neuropsychology. - Riddoch, M; Chechlacz, M; Mevorach, C; Mavritsaki, E; Allen, H; Humphreys, G (2010)
In this review, we discuss how neuropsychological impairments in visual selection can inform us about how selection normally operates. Using neuroanatomical and behavioral evidence on the disorders of neglect, extinction, and simultanagnosia, we propose functional and anatomical links between different aspects of visual selection and distinct sites in the posterior parietal cortex (PPC). This includes linking: (i) bottom-up attentional capture and the right temporo-parietal junction (TPJ); (ii) top-down segmentation of displays and the medial PPC; (iii) grouping, individuation and identification, and the inferior intra-parietal sulcus (IPS) bilaterally; and (iv) the suppression of saliency and the left IPS. In addition, when neuropsychological studies are combined with fMRI, there is evidence that these regions of the PPC interact with striate and extra-striate cortical areas, which respond to specific properties of stimuli. Selection should be viewed as an emergent property of a network of areas involving both ventral and dorsal cortex.